Effect of the Norepinephrine Transporter (NET) Inhibition on μ-Opioid Receptor (MOR)-Induced Anti-nociception in a Bone Cancer Pain Model - Hiroko Ono; Atsushi Nakamura; Tomoe Kanbara; Kazuhisa Minami; Shunji Shinohara; Gaku Sakaguchi; Toshiyuki Kanemasa (Elsevier, 2014)
Abstract.: Although norepinephrine transporter (NET) inhibition has an additional effect on μ-opioid receptor (MOR)-mediated anti-nociception in inflammatory and neuropathic pain, its effect on cancer pain is not well characterized. We investigated the additional effect of NET inhibition on MOR activation using a mouse femur bone cancer (FBC) pain model by comparing the antinociceptive effect of the dual-acting opioids tramadol and tapentadol and the clinically used MOR-targeted opioids oxycodone and morphine. The anti-nociceptive effects of subcutaneously administered opioids were assessed using the von-Frey filament test. Oxycodone (1 - 10 mg/kg) and morphine (5 - 50 mg/kg) dose-dependently exhibited potent anti-nociceptive effects, whereas tramadol (10 - 56 mg/kg) and tapentadol (10 - 30 mg/kg) exhibited partial effects. Rota-rod analyses of tapentadol at a higher dose (> 30 mg/kg) showed a significant decrease in motor coordination, which was partially recovered by pretreatment with MOR or α1-adrenoceptor antagonists. The partial anti-nociceptive effect of tapentadol (30 mg/kg) was completely suppressed by a MOR antagonist, but not by α1- or α2-adrenoceptor antagonists, suggesting that neither α1-adrenoceptor- nor α2-adrenoceptor-mediated pathways are involved in anti-nociception in the FBC model. We conclude that addition of NET inhibition does not contribute to MOR-mediated anti-nociception in bone cancer pain. Keywords:: femur bone cancer pain, norepinephrine transporter, oxycodone, tapentadol, μ-opioid receptor (MOR)